Disproportionation of Nitric Oxide at a Surface-Bound Nickel Porphyrinoid - Stredansky, Matus; Moro, Stefania; Corva, Manuel; Sturmeit, Henning; Mischke, Valentin; Janas, David; Cojocariu, Iulia; Jugovac, Matteo; Cossaro, Albano; Verdini, Alberto; Floreano, Luca; Feng, Zhijing; et al. (Angewandte Chemie International Edition, 2022)
Uncommon metal oxidation states in porphyrinoid cofactors are responsible for the activity of many enzymes. The F430 and P450nor co-factors, with their reduced NiI- and FeIII-containing tetrapyrrolic cores, are prototypical examples of biological systems involved in methane formation and in the reduction of nitric oxide, respectively. Herein, using a comprehensive range of experimental and theoretical methods, we raise evidence that nickel tetraphenyl porphyrins deposited in vacuo on a copper surface are reactive towards nitric oxide disproportionation at room temperature. The interpretation of the measurements is far from being straightforward due to the high reactivity of the different nitrogen oxides species (eventually present in the residual gas background) and of the possible reaction intermediates. The picture is detailed in order to disentangle the challenging complexity of the system, where even a small fraction of contamination can change the scenario.
CRIS-Team Scopus Importer:2022-04-01
Keywords: 2D Materials; Biomimetic Materials; Disproportionation; Nitrogen Monoxide; Porphyrins; Single-Atom Catalysts